Reverse logistics systems implemented in Brazil: a conceptual analysis using the AHP method - Schwarzer, Eduarda; Fagundes, Alexandre Borges; Possan Junior, Moacyr Carlos; Beuren, Fernanda Hänsch; Vaz, Caroline Rodrigues; Kobs, Fábio Fernando; Vieira, Cleide (OBSERVATÓRIO DE LA ECONOMÍA LATINOAMERICANA, 2025)
THIS IS AN ARTICLE PUBLISHED BY OBSERVATÓRIO DE LA ECONOMÍA LATINOAMERICANA (e-ISSN: 1696-8352) ON 2025-03-18, AVAILABLE ONLINE: https://doi.org/10.55905/oelv23n3-061 Abstract Reverse Logistics is a vital tool for reducing environmental impacts caused by improper handling of post-consumer goods. However, achieving the expected benefits from implementing Reverse Logistics Systems depends on their level of efficiency. In this context, considering the period from 2015 to 2016, this research aimed to analyze nine Reverse Logistics Systems established in Brazil, all with national coverage, and classify them based on their adherence to predefined performance requirements. Using the Analytical Hierarchical Process (AHP) method, the classification considered four analysis areas: Reverse Flow, Objectives and Goals, Number of Collection Points, and Waste Volumes to be Returned. As a result, performance factors were identified to improve the nine Reverse Logistics Systems studied, along with analyses and suggestions to contribute to the topic, which can also be applied to other similar systems.
Keywords: National Solid Waste Policy; Reverse Logistics Systems; Analytic Hierarchy Process (AHP); Performance Indicators; Performance Measurement